Impact of Rapid Transit Development on Urban Economic Growth: An Empirical Study of the Urban Agglomerations in China - Mao, Jinhuang; Tian, Qianwen; Lu, Chengpeng (Frontiers in Earth Science, 2022)
Transportation infrastructure and market integration play an important role in building China’s new development pattern of dual circulation. Taking 220 cities in 19 urban agglomerations in China as the study sample, this paper analyzes the impact of rapid transit development on urban economic growth from 2008 to 2019, and examines the heterogeneity of the difference in market integration capability in promoting urban economic growth based on Two-way fixed effects model. The main conclusions are as follows: (1) the improvement of travel convenience brought about by the development of expressways and high-speed railways significantly promoted urban economic growth; (2) market integration has significantly restricted the promotion of the construction of expressways and high-speed railways to urban economic growth. In other words, cities with less market integration have greater economic benefits from expressway and high-speed railway construction; (3) there is a certain substitution of the role of expressway and high-speed railway in promoting urban economic growth, and for cities that already have a relatively complete expressway network, further construction of high-speed railway will inhibit the promotion effect of expressway development on urban economic growth; (4) expressway and market integration have a stronger role in promoting urban economic growth in the eastern region than in the central and western regions, while high-speed railway and market integration promote the economic growth in the eastern region, and the impact on economic growth in the central and western regions is not significant. The findings of this paper have implications for optimizing the planning of expressway and high-speed railway construction and promoting high-quality regional development in China and other developing country.